Exploring motivation for learning using Hertzbergs two factor theory - Ibrahim, Irma Wahyuny; Mohamad Ghazali, Izlin; Syed Abdullah, Sharifah Aflinda; Rahmat, Noor Hanim; Abdul Hamid, Mohd Hafriz; Azhari, Siti Hajar Aisyah (Human Resource Management Academic Research Society, 2023)
Herzberg’s Motivator-Hygiene theory has been used for decades to measure individuals’ motivations for reaching their jobs’ achievements in their workplaces. Nevertheless, very limited studies are found on the relations of Herzberg’s Two-factor theory with learning motivation in education setting. This study aimed to identify the correlations between motivator (satisfiers) factors and hygiene (dissatisfiers) factors by utilizing motivational scales by Pintrich & De Groot in language learning classrooms. This quantitative study delved into what motivates students to learn and it used a 5-point Likert-scale survey, which was adapted from Herbeg’s (1964) two-factor theory and correlated with motivational scale by Pintrich & De Groot (1990). The instruments consisted of 3 sections. Section A has 4 items on demographic profile. Section B has 12 items on satisfiers and section C has 12 items on dissatisfiers. A purposive sample of 140 participants from a public university in Malaysia responded to the survey. The findings disclose that the application of motivator and hygiene factors from Herzberg’s Two-Factor Theory is feasible in finding the students’ motivations in language learning. Teachers and Curriculum writers need to design course works, authentic lesson plans, meaningful classroom activities and relatable tests to motivate students in language classrooms.